Financial Statement Comparability and Takeover Efficiency: A Pitch - Duong, Lien; Truong, Thu Phuong (Emerald, 2020)
Purpose: This paper aims to adopt the pitching research template of Professor Robert Faff for a proposed research project on financial statement comparability and takeover efficiency.